Flow Electrolyzer Mass Spectrometry with a Gas‐Diffusion Electrode Design - Hasa, Bjorn; Jouny, Matthew; Ko, Byung Hee; Xu, Bingjun; Jiao, Feng (Angewandte Chemie International Edition, 2021)
Operando mass spectrometry is a powerful technique to probe reaction intermediates near the surface of catalyst in electrochemical systems. For electrochemical reactions involving gas reactants, conventional operando mass spectrometry struggles in detecting reaction intermediates because the batch‐type electrochemical reactor can only handle a very limited current density due to the low solubility of gas reactant(s). Herein, we developed a new technique, namely flow electrolyzer mass spectrometry (FEMS), by incorporating a gas‐diffusion electrode design, which enables the detection of reactive volatile or gaseous species at high operating current densities (>100 mA cm−2). We investigated the electrochemical carbon monoxide reduction reaction (eCORR) on polycrystalline copper and elucidated the oxygen incorporation mechanism in the acetaldehyde formation. Combining FEMS and isotopic labelling, we showed that the oxygen in the as‐formed acetaldehyde intermediate originates from the reactant CO, while ethanol and n‐propanol contained mainly solvent oxygen. The observation provides direct experimental evidence of an isotopic scrambling mechanism. A new technique, flow electrolyzer mass spectrometry (FEMS), is developed by incorporating a gas‐diffusion electrode design. It enables the detection of reactive volatile or gaseous species at high operating current densities. The electrochemical carbon monoxide reduction reaction (eCORR) is investigated and the oxygen incorporation mechanism in the acetaldehyde formation determined.